Non-invasive diagnosis in a case of bronchopulmonary sequestration and proposal of diagnostic algorhythm - Caradonna, P.; Bellia, M.; Cannizzaro, F.; Regio, S.; Midiri, M.; Bellia, V. (Monaldi Archives for Chest Disease, 2016)
The case of a 43-year-old woman with intralobar pulmonary sequestration, Pryce type one, is presented. The medical history was characterised by recurrent bronchopneumonia, productive cough with purulent sputum and hemoptysis in the last three years. Diagnosis was made by CT angiography: multiplanar, maximum intensity projection and volume rendering reconstructions were visualised. A volume reduction of middle and lower lobe with multiple cyst-like bronchiectasis was detected and no evident relationship with tracheobronchial tree was pointed out. Reconstructions aimed at evaluating bronchial structures demonstrated no patency of middle and lower lobar bronchi. The study carried out after contrast medium infusion in arterial phase showed a vascular disorder characterised by an accessory arterial branch arising from the upper portion of thoracic aorta which, after moving caudally to pulmonary hilus with a tortuous course, supplied the atelectatic parenchyma. No anomalous venous drainage was detected. The patient underwent surgery with resection of two pulmonary lobes. CT compares favourably with other alternative imaging technique for pulmonary sequestration as multiplanar reconstructions allow not only the detection of supplying vessel, but also the accurate description of heterogeneous characteristics of the mass and adjacent structures. Finally an imaging-based diagnostic algorhythm is proposed.